A negative electrode sheet and its preparation method and application
By designing an array structure of current collector and electrode material blocks in the negative electrode sheet of a lithium-ion battery, and setting gaps and Pt particles between the electrode material layers, the battery's balance problem between high energy density, low temperature performance and cycle life is solved, and the battery's high energy density, excellent low temperature performance and long cycle life is achieved.
Patent Information
- Application Number
- CN202310314293.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-28
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-03-28
AI Technical Summary
It is difficult for existing lithium-ion battery negative electrode sheets to achieve a balance between high energy density, low temperature performance and cycle life, especially in low temperature environments, which can easily lead to loss of active lithium and reduced battery cycle life.
By designing the negative electrode sheet, a block of electrode material arranged on the surface of the current collector is used to adopt a current collector and an array, a gap is provided between the electrode material blocks, and Pt particles are provided between the upper active material layer and the lower active material layer to form a double-layer coating structure.
The battery has high energy density, excellent low temperature performance and long cycle life. It has achieved high energy density, excellent low temperature performance and long cycle life. It replenishes active lithium through the gap storage of electrolytes, alleviates material expansion, and improves electron and ion transmission capabilities.
Smart Images

Figure CN116387460B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries and relates to a negative electrode plate and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have been increasingly widely used in the field of consumer electronics due to their high energy density, environmental friendliness, and long cycle life. As the penetration rate of new energy vehicles exceeds 20%, the entire society has an increasing demand for power lithium-ion batteries, and batteries require increasingly higher energy density and cycle life.
[0003] Under the same design conditions, the increasing energy density of batteries requires higher coating quality, which will reduce the energy density of batteries. In addition, considering that many new energy vehicles are used in the northern hemisphere or in winter, the low-temperature performance requirements of batteries are getting higher and higher.
[0004] CN107230774A discloses a negative electrode sheet and a lithium-ion battery. The negative electrode sheet includes a negative electrode current collector and a negative electrode membrane. The negative electrode membrane is formed on one side or both sides of the negative electrode current collector. The negative electrode membrane includes: an inner active material layer, which is located on the negative electrode current collector and adjacent to the negative electrode current collector, and contains a negative electrode active material capable of deintercalating lithium ions; and an outer functional layer, which is located on the inner active material layer and on the side of the negative electrode membrane farthest from the negative electrode current collector, and the outer functional layer includes Super P and a binder, and does not contain a negative electrode active material capable of deintercalating lithium ions.
[0005] CN110416492A discloses a negative electrode plate, comprising a negative electrode current collector, a negative electrode material layer and a niobium titanium oxide layer which are stacked, wherein the negative electrode material layer is arranged between the negative electrode current collector and the niobium titanium oxide layer, and the niobium titanium oxide layer contains niobium titanium oxide, and the mass percentage of the niobium titanium oxide in the niobium titanium oxide layer is 70% to 90%.
[0006] The above scheme describes a negative electrode that is difficult to reconcile the contradiction between high energy density, low temperature performance and cycle life. The electrode with very slow ion and electron transmission will lead to poor low temperature behavior of the battery in a low temperature environment, and easily cause loss of low temperature active lithium, which will lead to poor cycle life of the battery. Therefore, it is very urgent to balance the energy density, low temperature performance and cycle life of the battery, which is of great significance to improving the driving experience and cost-effectiveness of new energy vehicles. Summary of the invention
[0007] The purpose of the present invention is to provide a negative electrode plate and a preparation method and application thereof. The present invention can well balance the high energy density, low temperature behavior and long cycle life behavior of the battery through special electrode design and modification, thereby improving the competitiveness of battery products.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a negative electrode plate, which includes a current collector and electrode material blocks arranged in an array on the surface of the current collector, gaps are arranged between the electrode material blocks, and the electrode material blocks include an upper active material layer, a lower active material layer and Pt particles arranged between the upper active material layer and the lower active material layer, the lower active material layer is close to the current collector, and Pt particles are arranged in the gaps.
[0010] In the negative electrode plate of the present invention, the constructed gaps directly penetrate to the bottom of the current collector. On the one hand, these gaps can store a large amount of electrolyte, thereby replenishing the consumption of active lithium in the battery during the cycle process and improving the cycle life of the battery. At the same time, these gaps can alleviate the expansion of the material, so that the electrode has a higher energy density and cycle stability.
[0011] Preferably, the current collector comprises carbon-coated copper foil.
[0012] Preferably, the shape of the electrode material block includes a square.
[0013] Preferably, the length of the electrode material block is 10 to 1000 mm, for example, 10 mm, 50 mm, 100 mm, 500 mm or 1000 mm.
[0014] Preferably, the width of the electrode material block is 50-300 mm, for example, 50 mm, 80 mm, 100 mm, 150 mm, 200 mm or 300 mm.
[0015] Preferably, the width of the gap is 0.2-1.5 mm, for example, 0.2 mm, 0.5 mm, 1 mm, 1.2 mm or 1.5 mm.
[0016] Preferably, the lower active material layer comprises silicon material, a conductive agent and a binder.
[0017] Preferably, the silicon material includes elemental silicon and / or silicon oxide.
[0018] Preferably, the upper active material layer includes a carbon material, a conductive agent and a binder.
[0019] Preferably, the carbon material comprises graphite.
[0020] Preferably, the conductive agent comprises conductive carbon black.
[0021] Preferably, the binder comprises polyvinylidene fluoride.
[0022] Preferably, the thickness of the lower active material layer is 8-9 μm, for example, 8 μm, 8.2 μm, 8.4 μm, 8.6 μm, 8.8 μm or 9 μm.
[0023] Preferably, the thickness of the upper active material layer is 130-132 μm, for example, 130 μm, 130.5 μm, 131 μm, 131.5 μm or 132 μm.
[0024] Preferably, the median particle size D50 of the Pt particles is 100-800 nm, for example, 100 nm, 200 nm, 400 nm, 600 nm or 800 nm.
[0025] Preferably, in the lower active material layer, silicon materials with a size greater than D50 account for more than 50%.
[0026] Preferably, based on the mass of the conductive agent in the upper active material layer and the lower active material layer being 100%, the mass of the conductive agent in the lower active material layer is greater than 50%.
[0027] The present invention adopts double-layer coating, and the material size > D50 in the bottom layer coating accounts for more than 50%, so that the relatively high pores can improve ion transmission. In addition, the bottom layer is closer to the current collector and has a stronger electron transmission capacity. When the bottom layer is 3D printed, the conductive carbon content is less than 50% of the total SP content.
[0028] In a second aspect, the present invention provides a method for preparing the negative electrode sheet as described in the first aspect, the preparation method comprising the following steps:
[0029] (1) Printing the lower slurry on the surface of the current collector through a 3D printing array, and magnetron sputtering Pt particles on the lower slurry and the gap;
[0030] (2) 3D printing the upper slurry layer on the lower slurry layer and drying it to obtain the negative electrode sheet.
[0031] In a third aspect, the present invention provides a battery, comprising the negative electrode sheet, the positive electrode sheet and the electrolyte as described in the first aspect.
[0032] Preferably, the electrolyte comprises a solvent, an electrolyte and an additive.
[0033] Preferably, the additive comprises benzenesulfonyl fluoride.
[0034] Benzenesulfonyl fluoride is added to the electrolyte of the present invention. This electrolyte additive can make the inner layer of the SEI film rich in LiF and the outer layer mostly organic components. In this way, the SEI film is more elastic and has higher strength, thereby improving the cycle stability and low-temperature behavior of the battery.
[0035] Preferably, the mass proportion of the solvent in the electrolyte is 20-35%, for example, 20%, 25%, 28%, 30% or 35%.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] (1) The electrode design of the present invention can increase the liquid retention of the battery, thereby increasing the cycle life of the battery. The negative electrode plate balances the low temperature performance and cycle life of the high energy density battery, expands the application conditions of the power lithium-ion battery and enhances the cost performance.
[0038] (2) The double-layer coating design described in the present invention places the silicon material close to the current collector and covers the carbon material negative electrode on the upper layer. During the charge and discharge process, the carbon material on the upper layer alleviates the expansion of the silicon material and reduces the active lithium consumption of the SEI film due to self-repair of the damage caused by material expansion, thereby improving the coulombic efficiency of the battery and increasing the cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a schematic diagram of the structure of the negative electrode plate described in Example 1 of the present invention, 1-Pt metal particles, 2-gap, 3-lower active material layer, 4-upper active material layer, 5-current collector. DETAILED DESCRIPTION
[0040] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0041] Example 1
[0042] This embodiment provides a negative electrode plate, and the negative electrode plate is prepared by the following method:
[0043] (1) 96.35 parts of elemental silicon, 2 parts of conductive carbon black and 1.65 parts of polyvinylidene fluoride are mixed with a solvent to obtain a lower layer slurry, wherein the proportion of materials with a size greater than D50 in the lower layer slurry is greater than 50%, 96 parts of graphite, 2.5 parts of conductive carbon black and 1.5 parts of polyvinylidene fluoride are mixed with a solvent to obtain an upper layer slurry, and the lower layer slurry array is printed onto the surface of the carbon-coated copper foil by 3D printing to obtain a lower layer slurry block with a length of 500 mm and a width of 200 mm, and the width between adjacent lower layer slurry blocks is 1 mm, and Pt metal particles with a particle size of 500 nm are magnetron sputtered onto the lower layer slurry blocks and gaps;
[0044] (2) 3D printing the upper slurry on the lower slurry block, covering the lower slurry block, and drying to obtain the negative electrode sheet. The structural schematic diagram of the negative electrode sheet is shown in FIG. Figure 1As shown, 1 is a Pt metal particle, 2 is a gap, 3 is a lower active material layer, 4 is an upper active material layer, and 5 is a current collector. In the negative electrode sheet, the thickness of the lower active material layer is 8.4 μm, and the thickness of the upper active material layer is 131.6 μm.
[0045] Example 2
[0046] This embodiment provides a negative electrode plate, and the negative electrode plate is prepared by the following method:
[0047] (1) 95.35 parts of elemental silicon, 2.5 parts of conductive carbon black and 2.15 parts of polyvinylidene fluoride are mixed with a solvent to obtain a lower layer slurry, wherein the proportion of materials with a size greater than D50 in the lower layer slurry is greater than 50%, 95 parts of graphite, 3 parts of conductive carbon black and 2 parts of polyvinylidene fluoride are mixed with a solvent to obtain an upper layer slurry, and the lower layer slurry array is printed onto the surface of the carbon-coated copper foil by 3D printing to obtain a lower layer slurry block with a length of 500 mm and a width of 200 mm, and the width between adjacent lower layer slurry blocks is 1 mm, and Pt metal particles with a particle size of 500 nm are magnetron sputtered onto the lower layer slurry blocks and gaps;
[0048] (2) 3D printing the upper slurry on the lower slurry block, covering the lower slurry block, and drying to obtain the negative electrode sheet. In the negative electrode sheet, the thickness of the lower active material layer is 9 μm, and the thickness of the upper active material layer is 131 μm.
[0049] Example 3
[0050] The only difference between this embodiment and the first embodiment is that the proportion of materials with a size greater than D50 in the bottom coating is less than 50%, and the other conditions and parameters are exactly the same as those in the first embodiment.
[0051] Example 4
[0052] The only difference between this embodiment and embodiment 1 is that the conductive agents in the upper and lower layers have the same mass, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0053] Comparative Example 1
[0054] The only difference between this comparative example and Example 1 is that no Pt metal particles are added, and other conditions and parameters are exactly the same as those in Example 1.
[0055] Comparative Example 2
[0056] The only difference between this comparative example and Example 1 is that no gap is set, and the lower layer slurry, Pt particles and upper layer slurry are directly coated. Other conditions and parameters are exactly the same as those in Example 1.
[0057] Comparative Example 3
[0058] The only difference between this comparative example and Example 1 is that the silicon material and the carbon material are mixed for coating, and the other conditions and parameters are exactly the same as those in Example 1.
[0059] Performance Test:
[0060] The negative electrode sheet manufacturing process is as follows: after coating and rolling, it is die-cut into a 100mm×192mm square electrode sheet, with a pole ear on the same side, and the pole ear size is 40mm×40mm; the positive electrode sheet uses the ternary material NCM811, the coating thickness is 136.5μm, and after rolling, it is cut into a 96mm×188mm square electrode sheet, with a pole ear on the same side, and the pole ear size is consistent with the negative electrode sheet. The diaphragm is 9+1+1μm diaphragm (double-sided glue coating, spray coating), Z-shaped stacking, 45 positive + 44 negative, the electrolyte is basic electrolyte (1M LiPF6+EC:DMC:EMC=1:1:1, mass ratio), and after hot pressing (1200kg, 90℃, 30s), it is assembled, injected, and sealed. It is pre-charged at 0.05C for 300min and 1 / 3C is converted into capacity. After the battery cell is left to stand, it is offline and tested as follows: (1) 25℃, charge and discharge test with a rate of 1 / 3C between 3.0V and 4.4V; (2) 25℃, 1C / 1C, 100% DOD cycle test; (3) The battery cell is fully charged at a constant current and constant voltage of 1 / 3C at 25℃, and discharged to 3.0V at a rate of 1 / 3C at -30℃. The test results are shown in Table 1:
[0061] Table 1
[0062]
[0063] It can be seen from Table 1 that from Examples 1-2, under the condition of not affecting the energy density, the capacity retention rate of the negative electrode plate of the present invention after 1500 cycles can reach more than 92.7%, and the low-temperature performance capacity retention rate can reach more than 92.9%. The negative electrode plate of the present invention has a relatively obvious improvement on the cycle performance and low-temperature performance of the battery cell. The double-layer coating process ensures the stability of the SEI film, thereby reducing the loss of active lithium; the active material gap optimizes the lateral expansion space of the fully filled material, and improves the wettability and cycle stability of the electrolyte.
[0064] From the comparison between Example 1 and Example 3, it can be seen that the present invention adopts double-layer coating, and the material size > D50 in the bottom layer coating accounts for more than 50%, so that the relatively high pores can improve ion transmission.
[0065] By comparing Example 1 and Example 4, it can be seen that the bottom layer of the negative electrode plate of the present invention is relatively close to the current collector and has a relatively strong electron transmission capability, so when the bottom layer is 3D printed, the conductive carbon content is less than 50% of the total conductive agent content.
[0066] By comparing Example 1 with Comparative Example 1, it can be seen that in the present invention, Pt metal particles are sputtered between the upper active material layer and the lower active material layer and on the gap, which can significantly improve the smoothness of electron transmission and improve the low-temperature charge and discharge performance of the electrode.
[0067] From the comparison between Example 1 and Comparative Example 2, it can be seen that the gaps in the negative electrode sheet of the present invention directly penetrate to the bottom of the current collector. On the one hand, these gaps can store a large amount of electrolyte, thereby replenishing the consumption of active lithium in the battery during the cycle process and improving the cycle life of the battery. On the other hand, this electrode rich in gaps and the electrode sputtered with a large number of conductive metal particles can improve the transmission behavior of electrons and ions and have excellent low-temperature behavior.
[0068] From the comparison between Example 1 and Comparative Example 3, it can be seen that the double-layer coating method adopted in the present invention can better synergistically exert the advantages of two different materials and complement the defects of the materials, thereby improving the energy density and effectively reducing the cost.
[0069] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A negative electrode plate, characterized in that: The negative electrode sheet comprises a current collector and an electrode material block arrayed on the surface of the current collector, gaps are arranged between the electrode material blocks, the electrode material block comprises an upper active material layer, a lower active material layer and Pt particles arranged between the upper active material layer and the lower active material layer, the lower active material layer is close to the current collector, and the Pt particles are arranged in the gap; The width of the gap is 0.2-1.5 mm; The lower active material layer is a combination of silicon material, conductive agent and binder; the upper active material layer is a combination of carbon material, conductive agent and binder; The thickness of the lower active material layer is 8-9 μm, and the thickness of the upper active material layer is 130-132 μm; The silicon material size in the lower active material layer is greater than D50, accounting for more than 50%; Taking the mass of the conductive agent in the upper active material layer and the lower active material layer as 100%, the mass of the conductive agent in the lower active material layer is less than 50%.
2. The negative electrode sheet according to claim 1, characterized in that: The current collector includes a carbon-coated copper foil.
3. The negative electrode sheet according to claim 1, characterized in that: The shape of the electrode material block includes a square.
4. The negative electrode sheet according to claim 3, characterized in that: The length of the electrode material block is 10-1000 mm.
5. The negative electrode sheet according to claim 3, characterized in that: The width of the electrode material block is 50-300 mm.
6. The negative electrode sheet according to claim 1, characterized in that: The silicon material includes elemental silicon and / or silicon oxide.
7. The negative electrode sheet according to claim 1, characterized in that: The carbon material includes graphite.
8. The negative electrode sheet according to claim 1, characterized in that: The conductive agent includes conductive carbon black.
9. The negative electrode sheet according to claim 1, characterized in that: The binder includes polyvinylidene fluoride.
10. The negative electrode sheet according to claim 1, characterized in that: The median particle size D50 of the Pt particles is 100-800 nm.
11. A method for preparing a negative electrode sheet according to any one of claims 1 to 10, characterized in that: The preparation method comprises the following steps: (1) Printing the lower slurry on the surface of the current collector through a 3D printing array, and magnetron sputtering Pt particles on the lower slurry and the gap; (2) 3D printing the upper slurry layer on the lower slurry layer and drying it to obtain the negative electrode sheet.
12. A battery, characterized in that: The battery comprises a negative electrode sheet, a positive electrode sheet and an electrolyte as described in any one of claims 1 to 10.
13. The battery according to claim 12, characterized in that The electrolyte includes a solvent, an electrolyte and an additive.
14. The battery according to claim 13, characterized in that The additive includes benzenesulfonyl fluoride.
15. The battery according to claim 13, characterized in that The mass proportion of the solvent in the electrolyte is 20-35%.
Citation Information
Patent Citations
Negative electrode piece and lithium ion battery
CN107230774A
Negative pole piece and electrochemical battery
CN110416492A
Lithium ion battery with silicon negative electrode system and electronic device
CN113745467A
Nonaqueous electrolyte solution, and nonaqueous electrolyte battery
CN113906530A
Nonaqueous electrolyte battery and manufacturing method of the same
JP2004103474A